PECULIARITIES OF DEVELOPMENT OF CITIES IN THE NORTHERN BORDER REGIONS OF AZERBAIJAN AND THE REGULATION OF THEIR DEVELOPMENT - ABDULLAEVA, Gulnara Islam (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The aim of the article is to investigate the features of the demographic and socio-economic development of cities in the northern border areas of Azerbaijan (Sheki, Zagatala, Gakh, Balaken, Gabala, Oguz, Khachmaz, Husar), to determine the direction of their perspective regulation in accordance with the trends that are taking place. The article uses such methods as historical overview, analysis of statistics of different periods, comparative analysis and descriptive method of demonstration of geographical objects. The study deals with taking into account the geostrategic significance of population resettlement in border areas, the importance of ensuring their economic, social and ecological development, regulating population migration processes, creating new jobs and implementing other social programs. The novelty of the article is that the directions of the demographic, socio-economic development of the cities are actually substantiated not only as the main supporting frames of the region, but also in terms of national interests, geopolitical and strategic situation. The article also identified socio-economic, natural-geographic, and other issues. factors affecting the location of cities in the northern border areas. mostly became possible during the years of Soviet power. The study says that cities are the largest economic centers of the country and the main centers of population settlement. The article scientifically analyzes geographical problems in Azerbaijan. Clarified features of Rego. It is concluded that it is clear from the article that scientific analyzes corresponding to geographical changes should be increased, such issues are considered comprehensively and universally in research.The study says that cities are the largest economic centers of the country and the main centers of population settlement. Before the establishment of Soviet power in Azerbaijan, only the cities of Sheki and Zagatala existed on this territory. Although these two settlements have long been formed as cities, they acquired city status only in 1840. And the cities of Balaken, Gakh, Gabala, Husar, Khachmaz, Oguz and other settlements located on the territory of administrative districts were created during the years of Soviet power and acquired the status of cities and towns. In general, the economic and geographical analysis of the development of the cities of the northern border regions allows us to reach the following conclusions and put forward a number of proposals: in the creation of urban settlements and the formation of their modern system, the leading role was played by the organizational-economic, social-administrative management function that they perform for the surrounding territories; аnother city-forming factor is the food industry, which is represented by small-scale enterprises that mainly rely on the processing of local agricultural raw materials.
Keywords: city; settlement; population; border areas; demographic potential